2018
DOI: 10.5812/jcrps.86930
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Core Stability Exercises at Home on Functional Ability and Chronic Low Back Pain (LBP) in Male Dentists

Abstract: Background: Lumbar Back Pain (LBP) as the most common musculoskeletal disorder in dentists has increased. Core stabilization exercises, as a new exercise method, can affect individual's abdominal and lumbar muscles. Given the deleterious effects of LBP on the performance of dentists. Objectives: This study aimed to assess the effect of core stabilization exercises at home on functional ability and chronic LBP in male dentists. Methods: The population of the present quasi-experimental study included all male de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…The previous studies showed that stabilization exercises are equally effective as the other interventions like whole-body vibration for the reduction in chronic low back pain [4,5]. Stability exercises and movement are dependent on the coordination of all the muscles adjacent to the lumbar spine and not only on the lumbar multifidi and transverse abdominal [34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The previous studies showed that stabilization exercises are equally effective as the other interventions like whole-body vibration for the reduction in chronic low back pain [4,5]. Stability exercises and movement are dependent on the coordination of all the muscles adjacent to the lumbar spine and not only on the lumbar multifidi and transverse abdominal [34].…”
Section: Discussionmentioning
confidence: 99%
“…The most common thought is that 5-10% of people develop chronic pain, the occurrence of chronic back pain [42-75%] and recurrence of back pain [24-84%] have been reported [3]. In different works of literature and articles, the prevalence of low back pain has been published several times [4,5]. Non-Specific Low Back Pain is a common disabling condition that affects not only a physical condition but also the psychological condition of the patient and is not caused by a serious pathology [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation